LAW AS AN INSTRUMENT OF SOCIAL TRANSFORMATION: A THEORETICAL AND EMPIRICAL STUDY OF THE ROLE OF LAW IN DRIVING CONTEMPORARY SOCIETAL CHANGE - I Wayan Kandia; I Wayan Wiryawan (CV. Tirta Pustaka Press, 2025)
This article explores the multifaceted role of law as a catalyst for social change, integrating theoretical insights with comparative empirical analysis. Drawing from classical sociological perspectives, critical legal studies, and interdisciplinary approaches, the paper examines how legal systems both reflect and shape evolving societal norms, values, and power dynamics. Through selected case studies—including civil rights reforms, environmental legislation, gender equality policies, and digital privacy laws—it highlights the conditions under which legal reforms succeed or fail in producing meaningful social transformation. The findings reveal that while law can institutionalize progressive change, its effectiveness depends on a range of factors, including political will, enforcement mechanisms, legal culture, and public legitimacy. The article argues that law functions most effectively as an instrument of social change when integrated with broader strategies of civic engagement, structural reform, and inclusive governance. Ultimately, the study underscores the necessity of a critical, context-sensitive, and future-oriented legal framework capable of addressing the complexities of contemporary social challenges.